The Rule of Jurisprudence Its Definition, its Origin and Development - Hussein , Zainab (Islamic Sciences Journal, 2023)
In the name of of Allah the Merciful Praise be to God. We praise Him, seek His help, and seek His forgiveness, and I bear witness that there is no god but Allah, and I bear witness that Muhammad is His servant and Messenger (PBUH), and upon all his family and companions, and those who follow them in goodness until the Day of Judgment. Then: The definition of jurisprudence rules as a science of a specific science has been the multiplicity of the sayings of scholars, ancient and modern. Their idiomatic definitions of the rule abounded based on the understanding of knowledge of its nature and functions. After examining these definitions and the criticisms leveled against them, the researcher tries to form a definition of the jurisprudential rule based on the definitions of those who preceded this study, trying to avoid the objections to which they were directed as: “a case of a jurisprudential college from which the rulings of its parts are known.” The science of jurisprudence has taken an evolutionary path in its inception, and it has not placed as a single science, but rather its concepts have been formed and formulated gradually.